Effects of cashew nut shell extract supplementation on enteric methane emissions and performance of natural feedlot heifers - Mehalic, Jasmine (My University, 2026)
Enteric methane (CH4) from feedlot cattle is both a greenhouse gas and an energetic loss, diverting 2 to 12% of dietary gross energy (GE). Cashew processing produces large quantities of waste, some of which can be refined into cashew nut shell extract (CNSE), a phenolic-rich supplement containing anacardic acid. This study evaluated effects of CNSE supplementation on methane emissions, animal performance, feeding behavior, and carcass characteristics in finishing heifers. Sixty crossbred heifers (initial body weight = 515 ± 9 kg) were assigned to 1 of 4 treatments (n = 15/treatment): 0, 2.5, 5.0, or 7.5 g CNSE/heifer daily for 105 d. The CNSE (DynOmik, Adisseo, Alpharetta, GA) contained at least 25% anacardic acid. The finishing diet contained (DM basis) 23% corn silage, 20% distillers' grains, 55% corn, and 3% vitamin/mineral supplement. Intake and feeding behavior were recorded using an Insentec Roughage Intake Control (RIC) system (Hokofarm, Emmeloord, The Netherlands). Methane emissions were measured using an automated head chamber system (AHCS; GreenFeed; C-Lock Inc., Rapid City, SD). Relative to control, supplementation with 2.5 g/d CNSE increased dry matter intake (DMI) (12.64 vs. 11.86 kg/d), whereas supplementation of 5.0 (11.00 kg/d) and 7.5 g CNSE/d (10.72 kg/d) reduced DMI (cubic P = 0.005). Average daily gain (ADG) decreased linearly (P = 0.02) with lower ADG at the higher CNSE inclusion rates (1.31, 1.34, 1.17, and 1.17 kg/d for 0, 2.5, 5.0, and 7.5 g CNSE/d). Gain:feed ratio was not affected by treatment (P ≥ 0.33). Heifers supplemented with 2.5 g CNSE/d had the greatest meal size (1.85 kg/meal), whereas meals per day increased with CNSE inclusion (linear P = 0.03) and eating rate decreased as CNSE inclusion increased (linear P = 0.03). Methane production (g/d) was not different among treatments (P ≥ 0.26). Methane yield (g/kg DMI), CH4 intensity (g/kg ADG), and Ym (% of gross energy) tended to exhibit a cubic response to CNSE supplementation, with the 2.5 g/d treatment numerically lower than the 0. 5.0, and 7.5 g/d treatments (cubic P = 0.095, 0.092, and 0.077, respectively). Carcass characteristics, including fat thickness, ribeye area, hot carcass weight, marbling score, quality grade, and calculated yield grade were not affected by treatment (P ≥ 0.33). Supplementation with CNSE altered feeding behavior and reduced growth performance at 5.0 and 7.5 g CNSE/d. Overall, CNSE supplementation did not reduce absolute CH4 production, but the nonlinear responses in CH4 yield, CH4 intensity, and Ym suggest that a low dose of 2.5 g/d may provide modest methane mitigation without compromising growth performance.
Keywords: Ruminant, Cashew, CNSE, Feedlot